Assessment of a training programme on detection of temporomandibular joint osseous changes applying pre‐defined 2D multiplane cone beam computed tomography reconstructions. (14th February 2018) - Iskanderani, D.; Alstergren, P.; Hellén‐Halme, K.
Summary: Objectives: Osseous changes in temporomandibular joint disorders (TMD) are common indications for cone beam computed tomography (CBCT). The number of such cases is increasing while a number of qualified oral radiologists is limited. This study investigated the usefulness of a training programme for general dental practitioners (GDPs) regarding temporomandibular joint (TMJ) osseous changes detection in CBCT images. Methods: We selected CBCT images of 35 TMD cases and chose 5 of them to use in training 7 GDPs on detecting osseous changes in the TMJ. In evaluation directly following training, GDPs assessed the 30 remaining cases. Three qualified radiologists served as reference standard. A 2‐month follow‐up of training comprising evaluation of the same cases. The cases are assessed according to Ahmad et al (Oral Surg Oral Med Oral Pathol Oral Radiol Endod, 107, 2009, 844) protocol of TMJ osseous changes in CBCT images. Results: Sensitivity and specificity of the CBCT protocol were high, except for some criteria that did not appear in the cases. Average observer sensitivity was 65% while specificity was 87%. Average correct individual response rate was 84%. Mean agreement among the GDPs was 73%. Observer performance had improved at the 2‐month follow‐up. Conclusion: The present educational programme could be a helpful material on recognising possible osseous changes of TMJ and it can be used as a part of a training programme for GDP and for specialist candidates.